Embolo/sclerotherapy for the treatment of hand arteriovenous malformations: a single-center retrospective cohort experience - Xueqiang Fan; Jianbin Zhang; Peng Liu; Zhidong Ye (Frontiers in Surgery, 2023)
PurposeTo retrospectively report our preliminary experience of treating hand arteriovenous malformations (AVMs) with embolo/sclerotherapy.Materials and methodsRetrospectively review the demographics, treatment detail, outcome data, and complications of 13 consecutive patients with hand AVMs from January 2018 to December 2021. We embolize the dominant outflow vein with elastic coils and then use absolute ethanol or polidocanol for intravascular sclerotherapy and bleomycin for interstitial sclerotherapy.ResultsYakes type II presents in four lesions, type IIIa in six, and type IIIb in three. A total of 29 treatment episodes were conducted for the 13 patients (1 episode for 3 patients, 2 for 4 patients, and 3 for 6 patients; the repeated treatment rate was 76.9%). The mean stretched length of coils for 1 treatment episode was 95 cm. The mean absolute ethanol dosage was 6.8 ml (range 4–30 ml). In addition, 10 ml of 3% polidocanol foam was injected and interstitial sclerotherapy with 150,000 IU bleomycin was performed on every patient. The post-operative arterial-dominant outflow vein pressure index (AVI) increased in the 29 procedures (6.55 ± 1.68 vs. 9.38 ± 2.80, P < 0.05). The Mann–Whitney U test showed that the post-operative AVI was higher in patients without re-intervention (P < 0.05). Local swelling occurred after all the procedures. Blistering occurred in 6 of the patients in 13 (44.8%) of the 29 procedures. Superficial skin necrosis occurred in 3 of the patients in 5 (17.2%) of the 29 procedures. The swelling, blistering, and superficial skin necrosis recovered within 4 weeks. No finger amputation occurred. The follow-up time was 6 months. The 6-month assessment of clinical improvement after the last treatment episode showed that 2 patients were cured, 10 were improved, and 1 remained unchanged. With regard to angiographic evaluation, 9 showed partial response and 4 complete response.ConclusionEmbolo/sclerotherapy can be effective and safe for hand AVM. The AVI increased significantly after embolo/sclerotherapy, and the index may be valuable in predicting recurrence in further study.